(untitled) (Colombia Medica, 1992)
The Nursing School of Universidad del Valle, Cali, Colombia, evaluated the first version of the new Master’s program, looking at the continuity of the main elements of the conceptual framework, the achievement of the professional profile, and the course’s objectives and the evaluation of the learning process, the student, and faculty’s contribution to health services, and the student’s and faculty’s satisfaction with the program. The data were collected using student, faculty, and health services personnel questionnaires. Of all of the students, 77%, and 73% of the faculty, considered that the main elements of the conceptual framework were always present during the program; 35% of the students and 56% of the faculty thought the professional profile was achieved. The course objectives were achieved for 65% of the students, and the learning was congruent with the course objectives for most students (76%). The curriculum evaluation allowed us to make some changes in the program in order to improve its quality. Participation of students, faculty, and personnel from health services is a strategy permitting the evaluation of the curriculum from different viewpoints.